Effect of Withania Somnifera as Feed Ingredient on Growth and Behavioral Changes of Laebo Rohita (Global Journal of Science Frontier Research, 2016)
The research was planned to study the effects of withania somnifera as feed ingredient on growth and behavioral changes of Labeo Rohita. For this purpose four aquarium were selected. Each aquarium was stocked with 15 fishes. Before stocking, fishes for each aquarium were treated with 5g/L sodium chloride (NaCl) to prevent fish from fungal infection. Fish sample were taken from Fish Hatchery which is situated at staina road. Two types of diets were given to fish one was normal diet which was given to fish and second was plant based diet which was obtained from withania somnifera. 1 st aquarium was served as control while others three served as experimental. After every one week fish was collected at regular intervals to check the growth parameters. Growth parameters such as fresh weight, fork length, total length and standard length were monitored weekly. The result showed that final average body weight was found 24.5, 26.2 and 28 in Withania somnifera. Water quality parameters like DO, Alkalinity, Carbon dioxide, pH, Temperature and chloride ions was also checked by taking water samples from the aquarium. Data analyzed with the help of analysis of variance to reach some conclusions.
Keywords: feed ingredient; NaCl; parameters; Carbon dioxide; pH